1991
DOI: 10.1111/j.1559-1816.1991.tb00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Crowding, Perceived Control, and Relative Power: An Analysis of Households in India1

Abstract: Data from rural villagers in India suggested that the perception of control was related to physical health but that household density (persons per room) had few effects. In a second study, separate interviews were conducted with the husband and wife in each of 167 households, which varied greatly in terms of number of household members and number of rooms. Results indicated that, once socio‐economic status and demographic factors were statistically held constant, household density had no effects. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
5
14
2
Order By: Relevance
“…To that extent, the finding generally corroborates the earlier empirical findings pertaining to control in the context of crowding and personal space. For example, the positive relationship between control and privacy preference is generally consistent with the negative relationship between perceived control and perceived crowding, reported in a study of Indian households (Ruback & Pandey, 1991).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To that extent, the finding generally corroborates the earlier empirical findings pertaining to control in the context of crowding and personal space. For example, the positive relationship between control and privacy preference is generally consistent with the negative relationship between perceived control and perceived crowding, reported in a study of Indian households (Ruback & Pandey, 1991).…”
Section: Discussionsupporting
confidence: 82%
“…They concluded that crowding reactions are actually attributions resulting from a loss of any of the three kinds of personal control. In the context of Indian households, perceived control (which would be more situation-specific than locus of control) was found to have positive effects in high-as well as low-density households (Ruback & Pandey, 1991). All of these forms of 'control' imply a control over the external environment or other people.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research indicates that the number of people with whom an individual interacts affects attitudes and behaviors (e.g., Baum & Valins, 1977;Paulus, 1988). Research from India indicates that household density is negatively related to psychological health (Ruback & Pandey, 1991) and females' reported physical symptoms (Ruback & Pandey, 1991), although there appears to be a stronger relationship between subjective crowding and health than between objective crowding and health (e.g., Fuller, Edwards, Vorakitphokatorn, & Sermsri, 1993). Moreover, the effects of density are often greatly reduced when psychological variables (e.g., perceived control) and environmental conditions (e.g., poverty) are held constant.…”
mentioning
confidence: 99%
“…Based on his research, Jain (1987) published a book on crowding and its consequences. A number of studies were conducted at Allahabad (Nagar & Pandey, 1987; Ruback & Pandey, 1991) to explore the environment‐cognition‐behaviour relationship. Another research programme on crowding, daily hassles, and coping was initiated at Pune University (Lepore, Evans, & Palsane, 1991).…”
Section: Expansion Of the Discipline: Dominant Research Themesmentioning
confidence: 99%